2015
DOI: 10.1210/en.2014-1572
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Growth Hormone Expression in Male GH Transgenic Mice Adversely Alters Bone Architecture and Mechanical Strength

Abstract: Patients with acromegaly have a higher prevalence of vertebral fractures despite normal bone mineral density (BMD), suggesting that GH overexpression has adverse effects on skeletal architecture and strength. We used giant bovine GH (bGH) transgenic mice to analyze the effects of high serum GH levels on BMD, architecture, and mechanical strength. Five-month-old hemizygous male bGH mice were compared with age- and sex-matched nontransgenic littermates controls (NT; n=16/group). Bone architecture and BMD were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 56 publications
1
12
0
Order By: Relevance
“…However, future studies using finite element analysis of the QCT images are needed in order to clarify if the pattern described in our report is associated with altered strength and resistance across the proximal femur in patients exposed to GH/IGF1 excess. Of note, overexpression of GH in mice is associated with accelerated bone turnover and low cortical vBMD of the vertebrae, femur, and tibia leading to deterioration of bone mechanical strength (27). Mazziotti et al (15) demonstrated that aBMD at the FN decreased in both active and controlled ACRO patients during a 3-year follow-up and this reduction significantly predicted vertebral fractures in controlled ACRO.…”
Section: Discussionmentioning
confidence: 99%
“…However, future studies using finite element analysis of the QCT images are needed in order to clarify if the pattern described in our report is associated with altered strength and resistance across the proximal femur in patients exposed to GH/IGF1 excess. Of note, overexpression of GH in mice is associated with accelerated bone turnover and low cortical vBMD of the vertebrae, femur, and tibia leading to deterioration of bone mechanical strength (27). Mazziotti et al (15) demonstrated that aBMD at the FN decreased in both active and controlled ACRO patients during a 3-year follow-up and this reduction significantly predicted vertebral fractures in controlled ACRO.…”
Section: Discussionmentioning
confidence: 99%
“…There was no difference in femoral length or width, so this likely indicates the cortical tissue perimeter has thinned, as has been shown in mice (Lim et al., 2015). This means less cortical bone was present in the femurs of squirrels on the CaOx than those on the control diet.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several models of overexpression of GHRH (6, 7), the human (h) (8–14) or bovine (b) GH in mice have demonstrated increased body size and skeletal gigantism (10, 1521). In this review we will focus on the skeletal phenotype of models overexpressing bGH, which activates the endogenous mouse GHR, as opposed to the hGH transgene, which activates both the GHR and the prolactin receptor.…”
Section: Global Impairment Of the Gh/igf-1 Axis Affects Body Size Andmentioning
confidence: 99%
“…All studies of transgenic mice with excess endogenous or transgenic bGH reported increases in bone size (length and diameter) and overall increases in bone mineral density (BMD). However, detailed analyses of skeletal properties revealed that systemic GH overexpression resulted in sex-specific and age-specific effects on the skeleton and impaired bone architecture and mechanical properties (15, 17, 19, 21). Overexpression of the hGHRH (20) resulted in systemic stimulation of endogenous GH and IGF-1 leading to initial increase in bone mass.…”
Section: Global Impairment Of the Gh/igf-1 Axis Affects Body Size Andmentioning
confidence: 99%
See 1 more Smart Citation